Financial Performance Evaluation of Selected CPSEs of India Through Dupont Analysis - Hothur, Sreevidya; Jayachandra Reddy, K. (Indian Journal of Finance, 2022)
The ability to create wealth for investors is one of the key performing indices of a business entity. Return on equity (ROE) measures this index, and DuPont analysis facilitates a critical evaluation of ROE. The present study attempted to establish the impact of DuPont factors on ROE and evaluated the financial performance of the selected companies. The empirical study was carried out on the financial data of three Maharatna central public sector enterprises doing business in the Indian fuel sector: Hindustan Petroleum Corporation Limited (HPCL), Indian Oil Corporation Limited (IOCL), and GAIL (India) Limited. Data were derived from the annual reports for a period of 10 years, from 2010–11 to 2019–20. Multiple linear regression was used to assess the degree of influence of DuPont factors on ROE. The results showed that the net profit margin of all the companies had more impact on ROE rather than the total asset turnover and equity multiplier . The results also proved that GAIL (India) Limited is a favored company for investors among the three companies considered in terms of consistency in ROE.